A lei Maria da Penha e o regime de informação das delegacias especializadas de atendimento às mulheres na Paraíba - Andrade, Kaliandra de Oliveira (2022)
Domestic and family violence against women can be considered a violation of human rights resulting from gender inequality and committed by present or former intimate companions (partners, spouses, and lovers); and typified in physical, psychological, sexual, patrimonial, and moral violence. In order to prevent, combat and punish domestic and family violence, victims can turn to specialized coping and care measures, such as the Maria da Penha Law (Law No. 11.340/2006) and the Specialized Police Stations for the Support of Women (DEAMs in its original acronym, which stands for "Delegacias Especializadas de Atendimento às Mulheres". In this context, the general objective of the research is to analyze the intervention of the Maria da Penha Law as a public policy in the information regime of DEAMs in Paraíba. This is a qualitative study based on the quadripolar methodology in terms of methodological characteristics. Documentary research and semi-structured interviews were conducted with social actresses for the collection of information: three sub-coordinators of DEAMs and a state manager of public policies for women. The results were interpreted using content analysis which was structured into eight categories related to the Maria da Penha Law, as well as the Information Regime, the network, and public policy. The results show that the Maria da Penha Law has influenced changes in the information regime of DEAMs - especially in information activities (Lives, Webinars, and Campaigns); in the artifacts (SOS Protected Woman and Online Police Report); in the updating of the Technical Norm for the Standardization of DEAMs; in policing procedures; and in the implementation of support policies by the state government - Integrated Patrol Program Maria da Penha. The Maria da Penha Law, therefore, acts as an information policy with affirmative measures to combat domestic and family violence - a law drafted and demanded by feminists and considered one of the three best laws in the world by UN Women, which includes guidelines for the work of governmental and non-governmental agencies, among other aspects within its scope. Although many measures are being taken to prevent domestic violence against women, there are still challenges in Paraíba: The lack of a specialized network for women, except in João Pessoa and Campina Grande - the two largest municipalities in the state; the lack of knowledge about the process of care and referral by professionals from local networks; the lack of a multidisciplinary team (Lawyer, Social Worker, and Psychologist) in DEAMs; victim-blaming; the need for continuing training of professionals in specialized and non-specialized services. As an intervention, the elaboration and publication of best practices in the fight against domestic violence developed by the specialized network are proposed, such as Provisional Shelter House; Online Renewal of Restraining Orders; creation of an application (Android OS) that allows victims to access the service network based on the violence suffered and their location (GPS).